Qazi Khairullah Padri's bilingual Pashto Urdu Dictionary “Khair-ul-Laghat” a Research and Critical Study (In the context of the technical principles of lexicography) - Munir Bukhari, Badshah; Sher, Ali (sourcecoder, 2022)
“Khair-ul-Laghat” is the first Pashto-Urdu dictionary, the first part of which (consisting of about 5220 words) has been published. The orthodoxy of the Pashto language is undeniable. It is disappointing to look at the early stages of this language, because as old as the Pashto language is, neither its literary capital was high nor did this ancient language reach the level which this language should have."Khair-ul-Laghat" is the first and earliest attempt of Pashto Urdu lexicography. The flaws in it are in place but the strengths in it cannot be ignored which the lexicographer has taken care of very well. The first strength of this dictionary is that Qazi Khairullah has divided it into chapters. The names of the various sports, household items, herbs, human organs, animals and birds are listed in the context. Taken as a whole, no dictionary is perfect. There must be some flaw in it because it is a difficult task and then for an individual this task becomes even more difficult. As far as "Khair-ul-Laghat" is concerned, it is the first dictionary of Pashto-Urdu languages. Not without flaws, nor can we call Qazi Khairullah's "Khair-ul-Laghat" a vast and extensive dictionary of Pashto Urdu, but still in an era in which no one pays attention to these two languages. He did pay attention. Qazi Khairullah took up the task. The flaws and shortcomings were in place but still this work regularly played a vital role in drawing the scholars and lexicographers towards the harmony and compatibility of these two languages.